2012
DOI: 10.1167/iovs.11-8410
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Multifocal Electroretinogram Amplitude, Visual Field Sensitivity, and SD-OCT Receptor Layer Thicknesses in Patients with Retinitis Pigmentosa

Abstract: In patients with RP, preserved cone photoreceptor function measured by mfERG amplitude and visual field sensitivity correlate well with the remaining thickness of the photoreceptor layer. All three measures show comparable relative loss beyond 3° eccentricity. In the fovea, SD-OCT outer retina thickness showed less relative loss than either mfERG or visual field sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
0
48
0
7
Order By: Relevance
“…7,8 In 2013, Birch et al 9 evaluated the progression rate of RP by serial measurements of the ellipsoid zone (EZ) band width using SD-OCT. They also showed that the mean rate of decline in the EZ band width (7%) translates into a mean rate of change of 13% for the equivalent area of functioning retina.…”
mentioning
confidence: 99%
“…7,8 In 2013, Birch et al 9 evaluated the progression rate of RP by serial measurements of the ellipsoid zone (EZ) band width using SD-OCT. They also showed that the mean rate of decline in the EZ band width (7%) translates into a mean rate of change of 13% for the equivalent area of functioning retina.…”
mentioning
confidence: 99%
“…In spite of progressive ONL thinning, most studies showed that the inner retinal layers remained histologically intact, including the inner nuclear layer (INL) and the ganglion cell layer [23,36]. In a clinical study, a decreased outer segment thickness without a significant decrease in the total retinal thickness suggested the presence of inner retinal thickening [37], and morphological studies reported less cellular loss in the INL than in the photoreceptor layers, which was consistent with the presentation of OCT images [38,39]. …”
Section: Inner Retinamentioning
confidence: 99%
“…6,7 This thinning of photoreceptor-attributable reflectivity layers in SD-OCT scans also corresponds to a reduction in multi-focal ERG amplitudes. 8 In short, the SW-AF rings are considered to reflect a transition between abnormal and normal retinal function, with function being relatively normal in retinal areas internal to the ring, reduced within the ring, and absent outside the ring. 913 These rings are not genotype specific and are observed in dominant, recessive, X-linked, and syndromic RP.…”
mentioning
confidence: 99%